Technologies of knowledge: the teaching of non-verbal language in the era of Web 2.0 - Sílvia Simões (2010)
In the context of Technological Issues in Education_ Classroom and Laboratory: Integration, the work that we propose, shows the main points presented to investigate possible interferences that occur in the subjects of education as creative elements in the production of images for different media / medium they use. Aware that technology and art have always coexisted in practice, we propose an analysis not to the results of experiments conducted by the artistic using a certain technology, but an analysis of the processes of construction and solidification of communication in certain learning contexts. We exclusively dedicate our attention to digital technology, and more specifically to the issues that the technology uses to communicate and it's representation in different contexts such as the analogical and digital [1]. We do not intend to do a chronological collection or present a set of situations and examples that demonstrate how technology has affected the perception and the construction of the world. In this sense, our proposal attempts to clarify some issues that seem relevant when talking about the process of using communications technology and information [2] applied to the teaching and learning to another process that is the drawing. What we study is whether these tools serve to communicate and who is expressed through non-verbal language, such as image, particularly drawn pictures. We do not refer to the use of the computer as a tool or as a means of dissemination. These issues are obviously outdated and the computer is used in drawing classes like any other tool available. The implications and changes that a tool like the computer might have not only to the communication between the participants in this case education but well as the development of procedural construction and solidification of an idea that deserves our attention. It is our obligation as teachers to be alert to the signs outside and to be able to provide students with mechanisms , tools and strategies that can support and develop their skills enabling them to produce, implement and develop expertise in future practice. Therefore, our contribution to the discussion at this meeting relates to the presence of digital technology in today's society and more specifically in the context: "Technology and art education."